2021
DOI: 10.1002/ehf2.13726
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function and its coupling to pulmonary circulation predicts exercise tolerance in systolic heart failure

Abstract: Aims Right ventricular (RV) dysfunction, pulmonary hypertension, and exercise intolerance have prognostic values, but their interrelation is not fully understood. We investigated how RV function alone and its coupling with pulmonary circulation (RV‐PA) predict cardio‐respiratory fitness in patients with heart failure and reduced ejection fraction (HFrEF). Methods and results The Evaluation of Resynchronization Therapy for Heart Failure (EARTH) study included 205 HFrEF patients with narrow (n = 85) and prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 41 publications
2
21
0
5
Order By: Relevance
“…Although some reports have previously shown that TAPSE 16–19 and TAPSE/PASP 20 could be affected by the presence low LVEF; to the best of our knowledge, direct comparison of different echo‐Doppler variables used for RV systolic function assessment with regards to LVEF, has never been done.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although some reports have previously shown that TAPSE 16–19 and TAPSE/PASP 20 could be affected by the presence low LVEF; to the best of our knowledge, direct comparison of different echo‐Doppler variables used for RV systolic function assessment with regards to LVEF, has never been done.…”
Section: Discussionmentioning
confidence: 96%
“…Even though, this newly validated noninvasive echocardiographic ratio measurement has been indisputably useful to assess RV-PA coupling noninvasively [12][13][14][15] ;data has continued to emerge showing its potential utility in heart failure patients, regardless the LVEF. 18,38,39 In fact, TAPSE/PASP ratio has also been found to be a much better prognostic predictor than either measure of TAPSE or PASP taken separately, particularly when assessing patients with severe mitral regurgitation referred for transcatheter mitral valve repair. 40 Even though TAPSE/PASP ratios were significantly different between normal and reduced LVEF patients in our studied population; this variable lack significance when examined in the stepwise multiple regression analysis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired systolic failure of the right ventricle, indicated by low TAPSE, cannot propel the blood against the elevated afterload and supply appropriate deoxygenized blood to the lungs [4,6]. Low levels of TAPSE and systolic pulmonary artery pressure, both of which indicate impaired right ventricular systolic function, were associated with poor exercise ability [12], a phenomenon of right ventricle-pulmonary artery uncoupling [3].…”
Section: Association Between Right Ventricular Function and Exercise ...mentioning
confidence: 99%
“…Very recently, the association between right ventricular function/reserve and exercise capacity has been investigated among various types of cohorts, including hospitalized 2 of 9 heart failure patients, systolic heart failure patients, and diastolic heart failure patients [3][4][5][6]. The association among candidates for cardiac rehabilitation remains uncertain.…”
Section: Introductionmentioning
confidence: 99%